Anatomical Variants in Pancreatic Irrigation and Their Clinical Considerations for the Pancreatic Approach and Surrounding Structures: A Systematic Review with Meta-Analysis - Juan José Valenzuela-Fuenzalida; Camila Ignacia Núñez-Castro; Valeria Belén Morán-Durán; Pablo Nova-Baeza; Mathias Orellana-Donoso; Alejandra Suazo-Santibáñez; Alvaro Becerra-Farfan; Gustavo Oyanedel-Amaro; Alejandro Bruna-Mejias; Guinevere Granite; Daniel Casanova-Martinez; Juan Sanchis-Gimeno (Medicina)
Background and Objectives: The pancreas receives blood through a complex network of multiple branches, primarily originating from the celiac trunk (CeT) and the superior mesenteric artery (SMA). This blood supply is structured into three main arterial groups, each serving different regions of the pancreas to effectively support its endocrine and exocrine functions. Materials and Methods: The databases Medline, Scopus, Web of Science, Google Scholar, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Latin American and the Caribbean Literature in Health Sciences (LILACS) were searched until January 2025. Methodological quality was evaluated using an assurance tool for anatomical studies (AQUA). Pooled prevalence was estimated using a random effects model. Results: A total of sixteen studies met the established selection criteria in this study for meta-analysis. Pancreatic irrigation variants presented a prevalence of 11.2% (CI: 7–14%) and a heterogeneity of 88.2%. The other studies were analyzed by subgroups, showing statistically significant differences in the following subgroups: (1) sample type—a larger sample of images analyzed in the included studies (p = 0.312), which did not show statistically significant differences; (2) geographical region (p = 0.041), which showed a greater presence in the Asian population studied, and this was statistically significant; and (3) sex (male or female) (p = 0.12), where there were no statistically significant differences. Conclusions: The discovery of variations in pancreatic irrigation is common due to the numerous blood vessels involved in supplying this vital organ. Understanding different vascular patterns (such as those from the splenic and mesenteric arteries) is crucial for surgical interventions on the pancreas. For transplant patients, a thorough vascular analysis of both the donor and recipient is essential. Variations can impact blood flow and compatibility, potentially leading to transplant rejection if not addressed. To enhance outcomes, it is recommended to develop more accurate imaging tools for pre-surgical analysis, necessitating ongoing research in this area.